CiiT 2010 Web Application - Kostoska, Magdalena; Ackovska, Nevena; Gjorgjievski, Dame (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2010)
This paper will give overview of the structure and the functionalities included in the CIIT 2010 web application. This application is an electronic tool that supports conference organisation including the following functionalities: electronic submission, review and grading of papers and abstracts, tracking the status of submitted papers and their categorisation, distinct roles like administrator, reviewer and author as well as changing between the roles (if the user of the system has more than one role) and content management.